aching the ESP course in the LMD system: Problems and Perspectives - Segueni, Lamri (Sciences humaines, 2014)
With the implementation of LMD system in the Algerian universities an ESP course was incorporated as an essential component of the curriculum of the LMD ‘licence’. This fact is dictated mainly by the nature of the LMD degree which is shaped by two main orientations, namely the academic and the occupational (professional) one.However,it must be mentioned that despite teachers great will and dedication, this course still faces serious hurdles that prevent it from reaching its objectives.      My paper will primarily deal with the teaching problems of the ESP course in the department of English, Biskra University. I will try to diagnose those problems in terms of 1) Course objectives, 2) Students' needs, 3) Teachers' experience, 4) Teaching materials and teaching methodology.     I will also try to bring my humble contribution as how to improve the teaching of this course through a number of pedagogical recommendations. Mots-clés  : Enseignant-Apprenant-Langue- Méthode- Interaction- Acteur- scène     إن تعليم اللغة الإنجليزية العلمية ليست ظاهرة جديدة إنما يعود تاريخها إلى السبعينات حيث كان يحتوي مقرر ليسانس اللغة الإنجليزية على مقياس يسمى اللغة الإنجليزية من اجل العلوم و التكنولوجية لكن ولأسباب مجهولة اختفى هذا المقياس تماما. اليوم مع تطبيق نظام ل م د في الجامعة الجزائرية ظهر هذا المقياس مجددا و بتسمية جديدة و كمكون أساسي في مقرر الليسانس و برجع سبب ظهوره إلي طبيعة ليسانس   ل م د التي قد تكون مهنية أو أكاديمية. و في كلتا الحالتين فإن تدريس اللغة الإنجليزية العلمية أصبح أساسيا بالنسبة للطلبة. مقالي هذا يتناول العوائق التي تواجه تعليم اللغة الإنجليزية العلمية في ليسانس ل م د. و سأحاول تشخيص هاته العوائق على مستوى أهداف المقياس , متطلبات الطلبة , خبرة الأستاذ ,المنهجية المتبعة و أخيرا المعدات و الوسائل التعليمية .